2013
DOI: 10.4103/0973-1482.113364
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma: Clinical experience from a tertiary care institute from North India

Abstract: Most common presentation in our series was locally advanced tumors. Most of these patients require adjuvant mediastinal radiation, which helps in significant loco-regional control. Systemic CCT benefits in inoperable, advanced and high-risk tumors. Risk-adapted and multimodality approach is the need of the hour to achieve good control rates while minimizing treatment related toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
5
13
0
Order By: Relevance
“…Global data have reported no sex predilection for TETs; however, the Indian studies had shown male predominance similar to the observation in the present series101415171823. Only two studies from India demonstrated a female-predominant population1316.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Global data have reported no sex predilection for TETs; however, the Indian studies had shown male predominance similar to the observation in the present series101415171823. Only two studies from India demonstrated a female-predominant population1316.…”
Section: Discussionsupporting
confidence: 83%
“…Its incidence in the Indian population has not been defined and in the power analysis carried out by Marchevsky et al 11, only 20 cases of thymomas were included from India. Among the Indian studies with more than 10 cases121314151617181920, Julka et al 18 had the largest sample with 71 cases (all thymomas) from the same centre; however, histomorphological spectrum was not described in this study. Except for studies by Vaideeswar et al 19 and Sundaram et al 20, none of the studies assessed the histomorphology of TET, especially thymic carcinomas.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…and the mean age in adults was (47.7 yrs.). [3][4][5][6][7][8][9][10][11][12][13] The remaining 4 (9.3%) cases were in paediatric age group (<16 yrs.) aged between 04-15 years (9.30%) with mean age of 9 years, of these four paediatric cases two were benign lesions diagnosed as thymic cysts (Fig-1a & b) aged 04 and 07 yrs.…”
Section: Resultsmentioning
confidence: 99%
“…The exact cause of thymomas remains unknown. These are typically slow-growing tumors that manifest themselves by local extension and when metastatic, the lesions are generally confined to the pleura, pericardium, or diaphragm [4-6]. The incidence of thymomas is estimated to be 1.3 cases per million population in the United States [7,8].…”
Section: Introductionmentioning
confidence: 99%